Influence of HDL particles on cell-cholesterol efflux under various pathological conditions - Asztalos, Bela F. (J Lipid Res, 2017)
It has been reported that low cell-cholesterol efflux capacity (CEC) of HDL is an independent risk factor for CVD. To better understand CEC regulation, we measured ABCA1- and scavenger receptor class B type I (SR-BI)-dependent cell-cholesterol efflux, HDL anti-oxidative capacity, HDL particles, lipids, and inflammatory- and oxidative-stress markers in 122 subjects with elevated plasma levels of triglyceride (TG), serum amyloid A (SAA), fibrinogen, myeloperoxidase (MPO), or β-sitosterol and in 146 controls. In controls, there were strong positive correlations between ABCA1-dependent cholesterol efflux and small preβ-1 concentrations (R(2) = 0.317) and SR-BI-dependent cholesterol efflux and large (α-1 + α-2) HDL particle concentrations (R(2) = 0.774). In high-TG patients, both the concentration and the functionality (preβ-1 concentration-normalized ABCA1 efflux) of preβ-1 particles were significantly elevated compared with controls; however, though the concentration of large particles was significantly decreased, their functionality (large HDL concentration-normalized SR-BI efflux) was significantly elevated. High levels of SAA or MPO were not associated with decreased functionality of either the small (preβ-1) or the large (α-1 + α-2) HDL particles. HDL anti-oxidative capacity was negatively influenced by high plasma β-sitosterol levels, but not by the concentrations of HDL particles, TG, SAA, fibrinogen, or MPO. Our data demonstrate that under certain conditions CEC is influenced not only by quantitative (concentration), but also by qualitative (functional) properties of HDL particles.